1989
DOI: 10.1002/bjs.1800760913
|View full text |Cite
|
Sign up to set email alerts
|

Changing patterns in gastric adenocarcinoma

Abstract: A retrospective study was performed on gastric cancer patients admitted to the Cancer Institute Hospital, Tokyo, during the periods 1961-65 (n = 1181) and 1980-84 (n = 1473). The aim of the study was to see whether changes had occurred in gastric cancer patients over the years with respect to histology and tumour localization and, if so, how they compared with reports from the West. The proportion of proximally localized primary tumour increased from 17 to 27 per cent (P = 0.008), and signet-ring cell carcinom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0
1

Year Published

1993
1993
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(30 citation statements)
references
References 9 publications
3
26
0
1
Order By: Relevance
“…dissection of nodes in positions [1][2][3][4][5][6][7][8][9][10][11], and dissection at least of the lower mediastinal nodes, at the First Division of General Surgery, Verona University, at the Institute of Surgical Sciences, Siena University, and at the First Division of General Surgery, Forli Hospital, Italy during the period January 1994 to April 1998.…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…dissection of nodes in positions [1][2][3][4][5][6][7][8][9][10][11], and dissection at least of the lower mediastinal nodes, at the First Division of General Surgery, Verona University, at the Institute of Surgical Sciences, Siena University, and at the First Division of General Surgery, Forli Hospital, Italy during the period January 1994 to April 1998.…”
Section: Patientsmentioning
confidence: 99%
“…Recent studies reported in the literature have revealed that, despite the decreasing overall incidence of gastric cancer in Western countries, there has been an increase in adenocarcinomas localized in the proximal stomach, particularly at the level of the cardia [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Sin embargo, en las últimas décadas se ha observado un incremento de la frecuencia de los tumores de cuerpo y fondo (cáncer gástrico proximal) y de la unión esófago-gástrica (7)(8)(9) , lo cual se sospecha está asociado al cambio en la prevalencia también del tipo histológico de cáncer gástrico hacia el tipo difuso (10,11) .…”
Section: Introductionunclassified
“…Some authors have also reported the same trend in foreign countries. (Craanen, Dekker, et al, 1992;Devesa, Blot, et al, 1998;Popiela, Kulig, et al, 2002) Nakajima, et al, 1989;Inoue, Tajima, et al, 1993) Kaneko et al have also reported finding significant decreasing trends for most age groups for papillary and mucinous adenocarcinomas. Tubular adenocarcinomas (the well-differentiated type) have shown a decreasing trend only in younger age groups.…”
Section: Discussionmentioning
confidence: 93%